TINJAUAN YURIDIS PERUBAHAN NAMA SESEORANG PADA AKTA KELAHIRAN DALAM HUKUM PERDATA - M. Ramadhan Matondang, Dani Sintara (YAPEKAM, 2023)
The purpose of civil law is to regulate everyday relations between residents or citizens. Civil law covers a person's marriage, divorce, death, inheritance, property, business and other civil actions. Name changes are part of population management which must be recorded by the population administration. Changing a person's name has legal consequences for civil law and state administration. Based on the research formulation, the research objective can be formulated as the causes of changes and additions to a person's name in the determination: No: 191/Pdt.P/2022 and the legal consequences of changing the name on the birth certificate according to the determination: No: 191/Pdt.P/2022/ PN Lbp?. The name change was carried out because the petitioner's husband left the divorce to die, so the petitioner wanted to change his name when writing the name, namely Riggia Anggi Khadijah Nasution to Anggi Nasution as written in the Marriage Book. The legal consequences of changing an adult's name on the legality of a child's legal status include changes to some authentic evidence. If a name change is made by someone who is an adult, of course the process will be longer, starting from changing the name on the birth certificate, changing the name on the Family Card (KK), changing the name of the KTP (Resident Identification Card), changing the name on the passport, changing the name school diplomas, and so on, as the legality of a person's name. This change began with changes to the birth certificate through a civil registration ]certificate. Then the name change is carried out based on the decision of the district court where the applicant is located.